Pleurocarpous mosses of Bangladesh, family Neckeraceae - I - Khatun, Hamida; Hadiuzzaman, Syed (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 47-56, 2003 (December)